The expression of MMP-11 in benign meningiomas [Benign meningiomalarda MMP-11 ekspresyonu] - (:unkn) unknown (Ege University Press, 2014)
The WHO categorises tumours based on their histological properties; however, this classification falls short of understanding their biological behaviours. Recently, there has been an increase in the number of studies on extracellular matrix components with the aim of understanding the biological behaviours of tumours. MMP-11 is a metalloproteinase from the MMP family that has a different expression pattern, mechanism of action, and substrate range compared with the other members of this family. Of the 55 benign meningioma cases examined, 29 were transitional, 16 were meningothelial, and 8 were fibroblastic in nature. In the meningotheliomatous cases, the MMP-11 expression score was high (75%), whereas it was low in the fibrous cases (87.5%). The Ki-67 levels in the cases with high MMP-11 expression scores were significantly higher than those of cases with low MMP-11 expression scores. Although there was no statistically significant correlation between recurrence and the MMP-11 expression score, 5 out of 7 cases with recurrence were found to have high MMP-11 expression scores. According to our study, MMP-11 is expressed in Grade I meningiomas. The level of MMP-11 expression appears to be high in the meningotheliomatous tumours and low in the fibrous subtypes. The tumours with a high level of MMP-11 expression also demonstrated high Ki-67 values.
Keywords: Extracellular Matrix; Meningioma; MMP11